1999
DOI: 10.1046/j.1365-313x.1999.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

A type 5 acid phosphatase gene from Arabidopsis thaliana is induced by phosphate starvation and by some other types of phosphate mobilising/oxidative stress conditions

Abstract: SummaryLow phosphorous availability, a common condition of many soils, is known to stimulate phosphatase activity in plants; however, the molecular details of this response remain mostly unknown. We puri®ed and sequenced the N-terminal region of a phosphate starvation induced acid phosphatase (AtACP5) from Arabidopsis thaliana, and cloned its cDNA and the corresponding genomic DNA. The nucleotide sequence of the cDNA predicted that AtACP5 is synthesised as a 338 amino acid-long precursor with a signal peptide.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
258
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(274 citation statements)
references
References 68 publications
14
258
1
1
Order By: Relevance
“…The function of purple plant phosphatases is unknown, the only real clue being the fact that they are inducible in some plants by phosphate deprivation. 25,71 It is possible that elucidation of their function may give insight into the role of TRAP in mammals. Novel structural features of recently discovered plant TRAP enzymes include membrane localization via a GPI anchor in an enzyme purified from duckweed.…”
Section: Enzyme Mechanism and Conservation Of Trap-like Enzymes Frommentioning
confidence: 99%
“…The function of purple plant phosphatases is unknown, the only real clue being the fact that they are inducible in some plants by phosphate deprivation. 25,71 It is possible that elucidation of their function may give insight into the role of TRAP in mammals. Novel structural features of recently discovered plant TRAP enzymes include membrane localization via a GPI anchor in an enzyme purified from duckweed.…”
Section: Enzyme Mechanism and Conservation Of Trap-like Enzymes Frommentioning
confidence: 99%
“…To monitor Piregulated gene expression, we used gene probes coding for an acid phosphatase (AtACP5), a Pi transporter (AtPT2), and a protein of unknown function (At4). These genes are induced by Pi limitation but are repressed in high Pi (Muchhal et al, 1996;del Pozo et al, 1999;Burleigh and Harrison, 1999). Seeds were germinated for 3 d on ϩPi medium and then transferred to ϩPi, ϪPi, and ϪPi/ϩPhi medium.…”
Section: Phi Selectively Represses Phosphate Starvationinducible Genementioning
confidence: 99%
“…These results are in agreement with studies in Brassica sp., which showed that Phi reduced the induction of phosphoenolpyruvate phosphatase, pyrophosphate-dependent phosphofructokinase, and highaffinity Pi uptake in Pi-limiting conditions by 40% to 90% (Carswell et al, 1996(Carswell et al, , 1997. We extended our studies to compare the effect of Pi and Phi on steadystate levels of Pi-responsive mRNAs, which encode a Pi transporter, AtPT2 (Muchhal and Raghothama, 1999), an acid phosphatase, AtACP5 (del Pozo et al, 1999), and an unknown gene product, At4 (Burleigh and Harrison, 1999). Our data clearly indicate that Phi represses Pi starvation-inducible gene expression at the transcript level.…”
Section: Table II Repression Of Pi Starvation-inducible Enzymes By Pmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to reducing arsenate, OsACR2.1 exhibits phosphatase activity. Phosphatase activities are commonly increased when internal levels of P are depleted (Duff et al 1991;del Pozo et al 1999;Baldwin et al 2001;Vance et al 2003). However, how OsACR2.1 expression is regulated when rice is P limited still needs to be determined.…”
Section: Introductionmentioning
confidence: 99%